2007
DOI: 10.1093/jac/dkm013
|View full text |Cite
|
Sign up to set email alerts
|

Low sale of antibiotics without prescription: a cross-sectional study in Zimbabwean private pharmacies

Abstract: The study revealed low sales of antibiotics without prescription, showing good adherence to the letter of the law. However, few respondents performed acceptably in relation to guidelines when considering information and advice for the tracer conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
68
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(72 citation statements)
references
References 28 publications
3
68
1
Order By: Relevance
“…Our results were in agreement with reported results from different studies in Jordan, Sudan and Greece [13,20,21,22]. On the other hand, amoxicillin was the most commonly selected antibiotic for self-medication [16,19,23,24 ].…”
Section: Discussionsupporting
confidence: 93%
“…Our results were in agreement with reported results from different studies in Jordan, Sudan and Greece [13,20,21,22]. On the other hand, amoxicillin was the most commonly selected antibiotic for self-medication [16,19,23,24 ].…”
Section: Discussionsupporting
confidence: 93%
“…39,64,67 Studies with patients simulated by actors showed that inappropriate antimicrobial dispensing by pharmacists without a prescription occurred frequently. [74][75][76][77][78][79][80][81][82][83]85 In low-income to medium-income countries, training of health-care workers as part of WHO's Integrated Management of Childhood Illness strategy has been shown to increase appropriate use of antimicrobials and decrease inappropriate use. [122][123][124][125] Non-physician health-care workers trained in integrated management of childhood illness might use antimicrobials more judiciously than physician providers.…”
Section: Discussionmentioning
confidence: 99%
“…Getting antibiotics directly from the pharmacy without a prescription is possible in Africa, South America, Asia as well as in many parts of Europe even when this practice is illegal [3][4][5][6][7][8][9][10][11] Previous research indicates that antibiotics are readily dispensed for urinary tract infections, sore throat, bronchitis and diarrhea. Many of these studies have addressed dispensing antibiotics without a prescription in therapeutic doses.…”
Section: Introductionmentioning
confidence: 99%